An overview on history of laboratory animal science in Asian countries (Journal of Laboratory Animal Science, 2024)
The time points of development of laboratory animal-based research and establishment of societies/associations for  laboratory animal science differ in the Asian part of the world. Some of the Asian countries do not have their own  associations and they are in the process of establishing them. In this context, we conceptualized the idea through this article  to provide an overview on initiation of laboratory animal-based research and establishment of associations or societies in  several different Asian countries.
Keywords: History; LAS; associations/societies; Asia